Phân tích hệ thống giáo dục đại học của Cộng hòa Pháp và một số khuyến nghị - Nguyễn, Hoàng Giang; Hoàng, Thị Minh Anh; Nguyễn, Lệ Hằng; Nguyễn, Hữu Khôi; Nguyễn, Thu Hà (Tạp chí Giáo dục, 2025)
In the context of globalization and increasingly deep international integration, higher education plays a key role in training high-quality human resources, meeting the requirements of socio-economic development of each country. Each higher education system in the world has its own characteristics, reflecting the historical, cultural and political context of each country, in which the higher education system of the French Republic stands out with its public nature, diverse stratification system and close connection between schools and businesses. The article analyzes the higher education system of the French Republic in terms of structure, scale, training levels, training forms, quality and costs, financial support..., thereby drawing lessons on the diversity, flexibility, internationality and autonomy of this education system. At the same time, the authors make a number of recommendations that are appropriate to the conditions and development context of Vietnam's higher education. Learning from advanced education systems in the world, including the French higher education system, can provide valuable lessons for our country's educational innovation process.